2021
DOI: 10.1248/bpb.b20-00643
|View full text |Cite
|
Sign up to set email alerts
|

Hsa_circ_0002060 Knockdown Ameliorates Osteoporosis by Targeting MiR-198-5p

Abstract: Osteoporosis (OP) is increasingly becoming one of a major health concerns all over the world. However, the limitations of current therapeutic drugs for OP are including considerable side effects and low efficacy. Therefore, it is required to develop new therapeutic drugs for OP. This study aimed to investigate the role of hsa_circ_0002060 in the regulation of osteoporosis.Osteoblast cells (hFOB 1.19) were transfected with hsa_circ_0002060 siRNA, following by stimulated with dexamethasone to mimic OP in vitro. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…We noticed that the expression of hsa_circ_0005778 was inconsistent with sequencing data; this may due to the limitation of sample size [ 25 ]. It has been reported that hsa_circ_0002060 depletion attenuates osteoporosis by regulating miR-198-5p[ 26 ]. circRNA_0006393 contributes to osteogenesis by targeting miR-145-5p/FOXO1 in glucocorticoid-induced osteoporosis [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…We noticed that the expression of hsa_circ_0005778 was inconsistent with sequencing data; this may due to the limitation of sample size [ 25 ]. It has been reported that hsa_circ_0002060 depletion attenuates osteoporosis by regulating miR-198-5p[ 26 ]. circRNA_0006393 contributes to osteogenesis by targeting miR-145-5p/FOXO1 in glucocorticoid-induced osteoporosis [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…circRNAs promoting OP circ_0002060 was also studied by Liu et al [25] .They tried to understand the function of this circRNA in the pathogenesis of OP, by studying its behaviour in osteoblast cells (hFOB 1. 19) treated with dexamethasone (DEX).…”
Section: Expression Of Circrnas In Op: the First Studiesmentioning
confidence: 99%
“…13) These small non-coding RNA molecules do not carry information about the structure of the protein but could regulate the gene expression by targeting selected mRNA that belong to the epigenetic mechanism. 14,15) MiRNAs, binding to untranslated region located in 3′ tail (3′-UTR) of mRNA, modulate its function through the impact on translation process, therefore miRNAs regulate gene expression post-transcriptionally. 16) In mammals, many researches have proved that miRNAs have important regulation functions in multidrug resistance (MDR) such as miR-125b, miR-491, miR-365, and miR-133a, [17][18][19][20] and several other miRNAs have been proved to be differentially expressed in sensitive and resistant lung cancer cells through next-generation sequencing in the miRNA database.…”
Section: Introductionmentioning
confidence: 99%